Investigating the Association between Healthy Eating Index and Early Childhood Caries in Iranian Preschool Children: A Case-Control Study - Maryam Mehrabkhani; Taraneh Movahhed; Mohsen Nematy; Melika Hoseinzadeh; Homeira Mohammadi (Journal of Nutrition and Food Security)
Background: Early Childhood Caries (ECC) is known as a main global dental problem in childhood period, which oral diet may play an important role in the occurrence of this complication. Thus, the present study aimed to evaluate the association between dietary Healthy Eating Index (HEI) and ECC in children living in Mashhad, Iran. Methods: In the current case-control study, 732 preschool children (aged 3–6 years) were examined for dental caries and then categorized into two groups of children with ECC, or who were Caries-Free (CF). Then, the HEI was measured by analyzing a validated food frequency questionnaire, which their parents were requested to complete. The association between HEI score and the prevalence of ECC was determined using logistic regression analysis. Results:  The HEI for CF group was significantly higher than ECC group (P<0.001, CI 95%: 57.58-67.93 vs. 51.72-65.49), respectively). The mean scores of grain, milk, fruits, vegetables, and meat groups were significantly higher in CF group (P<0.001).  Children in CF group were also more compliant with recommended intake of total fat (P<0.01) and cholesterol (P<0.001). Furthermore, CF children had a significantly more diverse food item intake (P<0.001). It is noteworthy to mention that, with each unit increase in HEI score, the odds of ECC decreased by 0.04 (P=0.01, OR=0.04). Conclusion: Caries prevalence in preschool children could be prevented by enhancing food quality.